1995
DOI: 10.1007/bf00021192
|View full text |Cite
|
Sign up to set email alerts
|

Intron-dependent transient expression of the maize GapA1 gene

Abstract: Transient expression experiments show that the maize GapA1 promoter exhibits a requirement for sequences contained within intron 1 and surrounding exon border regions for expression in maize Black Mexican Sweet cells. Maize GapA1-promoter constructs lacking intron 1 are inactive. Intron 1 and its exon border sequences, when reintroduced into constructs lacking introns, restore gene activity whereas intron 2 and its exon borders to not. The minimal promoter so defined encompasses roughly 250 bp upstream of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Characterization of the promoter of this gene, fused to the uidA-coding region (which encodes GUS), has shown that greater expression in monocot species occurs when the first intron from tpi is included in constructs [12]. This phenomenon has been observed in monocots for several genes including alcohol dehydrogenase 1 (Adhl) from maize [3,6,7], the maize GapA1 gene [4], and rice actin 1 [8]. It does not appear that intron enhancement is essential for expression from all monocot genes as not all monocot genes have introns (for example the rice gene RCg2, [10]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of the promoter of this gene, fused to the uidA-coding region (which encodes GUS), has shown that greater expression in monocot species occurs when the first intron from tpi is included in constructs [12]. This phenomenon has been observed in monocots for several genes including alcohol dehydrogenase 1 (Adhl) from maize [3,6,7], the maize GapA1 gene [4], and rice actin 1 [8]. It does not appear that intron enhancement is essential for expression from all monocot genes as not all monocot genes have introns (for example the rice gene RCg2, [10]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when the intron is placed outside of the transcriptional unit (i.e. when the intron is placed 5' of the promoter, or 3' of the polyadenylation signal) enhancement of gene expression is not observed [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…The observation that some introns stimulate gene expression was first made in animal systems and extended to plants when Callis et al (1987) demonstrated that the maize (Zea mays) Adh1 first intron increased expression of several genes. Other maize introns that have been shown to increase expression include the Bz1 intron (Callis et al, 1987), Hsp82 first intron (Silva et al, 1988), Sh1 first intron (Vasil et al, 1989), Adh1 introns 2 and 6 (Mascarenhas et al, 1990), actin third intron (Luehrsen and Walbot, 1991), GapA1 first intron (Donath et al, 1995), Ubi1 first intron (Vain et al, 1996), and the RpoT fourth intron (Bourdon et al, 2001).Plant introns that stimulate expression have been documented in petunia (Petunia hybrida; Dean et al, 1989;Vain et al, 1996) Leon et al, 1991;Fu et al, 1995aFu et al, , 1995b, Arabidopsis (Rose and Last, 1997; ChaubetGigot et al, 2001), soybean (Glycine max; Kato et al, 1998), and tobacco (Nicotiana tabacum; Plesse et al, 2001). The approximately 2-to 10-fold range of intron-mediated enhancement usually seen in dicots is much less than increases observed in monocots, which can be more than 100-fold (for review, see Simpson and Filipowicz, 1996).…”
mentioning
confidence: 99%
“…The observation that some introns stimulate gene expression was first made in animal systems and extended to plants when Callis et al (1987) demonstrated that the maize (Zea mays) Adh1 first intron increased expression of several genes. Other maize introns that have been shown to increase expression include the Bz1 intron (Callis et al, 1987), Hsp82 first intron (Silva et al, 1988), Sh1 first intron (Vasil et al, 1989), Adh1 introns 2 and 6 (Mascarenhas et al, 1990), actin third intron (Luehrsen and Walbot, 1991), GapA1 first intron (Donath et al, 1995), Ubi1 first intron (Vain et al, 1996), and the RpoT fourth intron (Bourdon et al, 2001).…”
mentioning
confidence: 99%
“…For yeast it has been suggested that 5' introns may be implicated in the control of pre-mRNA abundance via the nonsensemediated mRNA decay pathway [26]. Another possibility may be the implication of 5' introns in transcriptional control of gene expression for which some evidence has been obtained with intron 1 of gene GapA1 from maize [11].…”
Section: Intron Loss In Rhodophyte Genes By Cdna Mediated Gene Convermentioning
confidence: 99%